An overview of the shallow-water calcified hydroids from Brazil (Hydrozoa: Cnidaria), including the description of a new species - Amaral, Fernanda M. D.; Steiner, Andrea Q.; Broadhurst, Matt K.; Cairns, Stephen D. (Zootaxa, 2008)
Five species of calcified hydroids occur in shallow waters along the Brazilian coast: four milleporids –Millepora alcicornis Linnaeus, Millepora braziliensis Verrill, Millepora nitida Verrill, and a new species, Millepora laboreli – and one stylasterid – Stylaster roseus (Pallas). Compared to the scleractinian corals, the calcified hydroids of Brazil have received little attention. Nevertheless, Milleporidae are an important component of Brazilian reefs, with colonies that can reach up to 2 m in diameter. Among the aspects that have been studied for Millepora spp, their distributions and skeletal morphometries are the most distinctive. Due to their complex taxonomy, several morphometric characters have been used to facilitate their identification. Molecular systematics has also been used as a complementary technique to traditional taxonomic tools. Other aspects of Brazilian Millepora spp, such as their nematocysts, medusae and ecology, have received less attention; nevertheless, the few existing studies reveal several remarkable features of this genus. Comprehensive studies of Brazilian stylasterids are still lacking.